Homochiral Self‐Sorting During Macrocycle Formation and their Chiroptical Properties - Diptiprava Sahoo; Dr. Soumen De (ChemistryOpen)
Abstract Several BINOL‐derived C2‐symmetric aldehydes were synthesized to investigate chiral self‐sorting phenomena during macrocycle formation in the presence of aliphatic and aromatic bisamines. While self‐sorting was unsuccessful with aliphatic amines, aromatic amine dictated complete homochiral self‐sorting, confirmed by 1H NMR analysis and molecular modelling. Additionally, the impact of macrocyclization on the chiroptical properties of these macrocycles was examined. The Cotton effects band red‐shifted for aromatic amines owing to extended conjugation. Notably, a substantial increase in specific rotation was observed upon macrocycle formation.